Medea of Euripides and the Old Testament: Cultural critical remarks with special reference to the background of the Septuagint - Daphnē, Euangelia (HTS teologiese studies, 2020)
This article expands upon the range of options and methods of some of my earlier studies on Euripides and the Old Testament. These studies have sought to discover similar linguistic features and concepts in the texts of Euripides and the Old Testament, and to discuss how Euripidean tragedies can be read as Greek responses to Hebrew anthropological beliefs, more specifically as poetic-philosophical approaches to the anthropo-theological narratives of Genesis 2–4 and related biblical texts. These biblical texts probably transmitted through improvised oral or written Greek translations preceding the Septuagint (LXX), reorganise and transform the meaning of Hebrew expressions. This article presents the basic problems and aspects of a cultural-critical and comparative analysis and illustrates them with shared motifs from Medea, one of the eight Euripidean tragedies named after a female protagonist, and the Old Testament, thus expanding the boundaries of the traditional historic-critical exegesis.Contribution: The article contributes to the investigation of the background of the Septuagint from a cultural critical perspective with special reference to the Euripidean tragedies.